Ethical challenges and practical strategies. (Office for Learning and Teaching, 2016)
Booklet emanating from a project that researched OLT-funded projects that have been delayed or stalled because of 'research ethics review problems'. It includes a collection of case studies of research in scholarship of learning and teaching (SoTL). For some case studies, there is added expert commentary from experienced researchers. Some cases are presented as works in progress, so that, over time, further examples and commentary can be added. Case-based approaches encourage ethical practice among researchers. By stimulating moral imaginations, they can help researchers recognise ethical issues, develop analytical skills, respect the points of view of other people, take personal responsibility for decision-making and negotiate with regulatory bodies.